NILAI-NILAI PENDIDIKAN DALAM AL-QUR’AN SURAT LUQMAN AYAT 12-19 (Studi Tafsir Al-Qur’an Al-‘Azhim Karya Ibnu Katsir) - Putri Alifah Khofiyatur Rido; Yuyu Wahyudin; kurnia illahi; Zahra eka sawitri; Arifah Nur Rahmah; Yayah, Husheini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the values of Islamic education contained in Surah Luqman verses 12–19 based on Ibn Kathir’s Tafsir al-Qur’an al-‘Azhim. The study aims to identify the educational values contained in these verses and examine their implications for Islamic educational practice. This study employs a qualitative library research method using a tahlili (analytical) approach. The primary source is Ibn Kathir’s Tafsir al-Qur’an al-‘Azhim, supported by relevant secondary sources on Qur’anic interpretation and Islamic education. The findings indicate that Surah Luqman verses 12–19 contain seven interrelated educational values: tauhid (monotheism), gratitude, filial piety, worship, social responsibility, patience, and noble character (akhlak). These values are conveyed through Luqman’s compassionate advice to his son, beginning with the strengthening of faith and continuing with worship, social responsibility, and moral formation. Ibn Kathir’s interpretation demonstrates that tauhid serves as the fundamental basis for the formation of worship and character. The findings further indicate that these educational values can be reconstructed into educational practice through strengthening the role of teachers as exemplary murabbi, integrating knowledge, faith, worship, and character within the curriculum, and internalizing tawadhu (humility) as an important character value. Thus, Surah Luqman verses 12–19 provide a comprehensive foundation for Islamic education that integrates faith, worship, morality, and social responsibility in the formation of students’ character Keywords: Educational values, Surah Luqman, Ibn Kathir’s Tafsir